2021
DOI: 10.3390/s21134402
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ROI Extraction Method Based on the Characteristics of the Original Finger Vein Image

Abstract: As the second generation of biometric technology, finger vein recognition has become a research hotspot due to its advantages such as high security, and living body recognition. In recent years, the global pandemic has promoted the development of contactless identification. However, the unconstrained finger vein acquisition process will introduce more uneven illumination, finger image deformation, and some other factors that may affect the recognition, so it puts forward higher requirements for the acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The ROI extraction stage is crucial in practical applications. The finger vein ROI extraction methodology can adopt the technique detailed in reference [46], which proposes a novel method for finger vein images. This method includes a horizontal Sobel operator, a contour-based edge detection method, and a gradient detection operator with a large receptive field.…”
Section: Finger-vein Public Datasetsmentioning
confidence: 99%
“…The ROI extraction stage is crucial in practical applications. The finger vein ROI extraction methodology can adopt the technique detailed in reference [46], which proposes a novel method for finger vein images. This method includes a horizontal Sobel operator, a contour-based edge detection method, and a gradient detection operator with a large receptive field.…”
Section: Finger-vein Public Datasetsmentioning
confidence: 99%
“…The study performed on the MMCBNU_6000 dataset revealed that the highest classification accuracy using the CNN-RAW model is 91.72%. In the study performed by Lu et al [31] in 2021, a new region of interest extraction method was proposed depending on the characteristics of the FV image and compared with some representative methods. The equal error rates calculation of the proposed method on the MMCBNU_6000 dataset is 5.49% by using maximum curvature, and 3.33% by using repeated line tracking feature extraction method.…”
Section: Related Workmentioning
confidence: 99%
“…Finger vein ROI extraction involves isolating and clipping out the finger region with the most abundant vein pattern and eliminating undesirable areas from the raw images. In this work, we utilized the method proposed by Lu et al (2021) , which is based on the characteristics of the original finger vein image. Their algorithm starts by searching for the finger edges based on the finger contour imaging characteristics.…”
Section: Introductionmentioning
confidence: 99%